Perspectives and development sceneries for rural communities: a study case in Sora, Boyacá, Colombia (2012)
Domestic statistics show that Boyacá is the second poorest department in Colombia. This information differs with reality since this territory has one of the most productive human resources and a wide variety of natural resources. According to these characteristics there should not be such low human, economic, and social living conditions for its population. The socio-economic situation becomes even worse for people who live in minor cities, especially in the smallest towns where there are not conditions to produce and generate an excellent life quality.  People survive in poverty and deprivation with a high level of dependency which does not allow them to reach development for a dignified life. This is the case of Sora, a small town in Boyacá, where, due to its particular conditions of natural and human resources scarcity, the socio-economic circumstances are even more serious. This complex problem caused this investigation to determine possible solutions to poverty, indigence, low level of education, lack of health prevention programs, and low production of goods and services, as elements that have an effect on the development of rural community.